Clinical Outcome of Patients with Complete Pathological Response to Neoadjuvant Chemoradiotherapy for Locally Advanced Rectal Cancers: The Indian Scenario - Snita Sinukumar; Prachi Patil; Reena Engineer; Ashwin Desouza; Avanish Saklani (Gastroenterology Research and Practice)
Introduction. Neoadjuvant chemoradiotherapy and total mesorectal excision are considered the standard treatment for locally advanced rectal cancer. Various studies have reported pathological downstaging and a complete pathological response rate of 15%–27% following neoadjuvant chemoradiotherapy which has translated into improved survival. We endeavour to determine the clinical outcome of patients attaining a complete pathological tumor response following neoadjuvant chemoradiotherapy in the Indian setting where most of our patient population is younger and presents with aggressive tumor biology. Materials and Methods. Clinicopathological and treatment details were recorded for 64 patients achieving pathological complete response from 2010 to 2013. Disease-free survival (DFS), overall survival (OS), and locoregional and systemic recurrence rates were evaluated for these patients. Results. After a median follow-up of 30.5 months (range 11–59 months), the 3-year overall survival (OS) was 94.6% and the 3-year disease-free survival (DFS) was 88.5%. The locoregional and systemic recurrence rates were 4.7% and 3.1%, respectively. Conclusion. In the Indian subcontinent, despite younger patients with aggressive tumor biology, outcome in complete responders is good.